2022
DOI: 10.1007/978-3-030-92377-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Migration

Abstract: In the context of the growing global middle class, and the ageing of the baby boomer generation, an increasing number of migrants with accumulated wealth from advanced economies are relocating to economically less developed or more peripheral countries to improve their quality of life. Migration of the middle-classes and the relatively affluent is embedded in the same globalising processes and social transformations in production and processes of accumulation that have reshaped labour migration (Hayes, 2021; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Three key forms of migration have been identified that encapsulate the majority of migration: labour migration, which includes the movement of both 'high-skilled' and 'low-skilled' workers, family migration for marriage or the existence of 'transnational families' living in different places, and humanitarian migration, which includes refugees and asylum seekers, survivors of human trafficking, unaccompanied minors and internally displaced people. Other forms of migration include lifestyle migration, where people move for a perceived increased quality of life over economic benefits, student migration, and irregular migration, defined as movement outside of the laws or regulations governing countries of origin, transit or destination (McGarrigle 2022;Sironi et al 2019;Talleraas 2022). Whatever the reason for migration, the interconnectedness of our modern world, facilitated by advancements in transportation and communication, has facilitated a complex web of global migration patterns, and the dynamics of contemporary migration are more intricate and far-reaching than ever before (World Economic Forum 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Three key forms of migration have been identified that encapsulate the majority of migration: labour migration, which includes the movement of both 'high-skilled' and 'low-skilled' workers, family migration for marriage or the existence of 'transnational families' living in different places, and humanitarian migration, which includes refugees and asylum seekers, survivors of human trafficking, unaccompanied minors and internally displaced people. Other forms of migration include lifestyle migration, where people move for a perceived increased quality of life over economic benefits, student migration, and irregular migration, defined as movement outside of the laws or regulations governing countries of origin, transit or destination (McGarrigle 2022;Sironi et al 2019;Talleraas 2022). Whatever the reason for migration, the interconnectedness of our modern world, facilitated by advancements in transportation and communication, has facilitated a complex web of global migration patterns, and the dynamics of contemporary migration are more intricate and far-reaching than ever before (World Economic Forum 2022).…”
Section: Introductionmentioning
confidence: 99%